2000
DOI: 10.1038/sj.cdd.4400702
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle progression and apoptosis after irradiation in an acidic environment

Abstract: We investigated the effect of an acidic environment on the radiation-induced G2/M arrest and apoptosis using RKO×C human colorectal cancer cells expressing wild-type p53 and RC10×1 cells, a subline of RKO×C cells deficient in p53 as well as p53 +/+ MEFs and p53 7/7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…However, increased glycolysis caused by HIF-1␣ may not be beneficial for tumor cells which already exhibit elevated glycolysis due to other genetic mutations, since increased fermentation results in overproduction of lactic acid. Several reports indicate that p53 is only activated to promote apoptosis and cell cycle arrest in acidic environments (71,74,87,109). Furthermore, the hypoxia-inducible proapoptotic gene bNIP-3 is also only active in acidic environments (9,96).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increased glycolysis caused by HIF-1␣ may not be beneficial for tumor cells which already exhibit elevated glycolysis due to other genetic mutations, since increased fermentation results in overproduction of lactic acid. Several reports indicate that p53 is only activated to promote apoptosis and cell cycle arrest in acidic environments (71,74,87,109). Furthermore, the hypoxia-inducible proapoptotic gene bNIP-3 is also only active in acidic environments (9,96).…”
Section: Discussionmentioning
confidence: 99%
“…Although HIF-2␣ does not regulate glycolytic genes, it does stimulate GLUT-1 expression in 786-O and HEK293 TET-on cells. Increased glucose transport into cells may provide a survival advantage, since glucose is required for Akt-mediated inhibition of cytochrome c release and apoptosis (30,74). Akt has been shown to be activated by hypoxia (1,8,16,31,48,76).…”
Section: Discussionmentioning
confidence: 99%
“…Both lactate acid and H 2 CO 3 production lead to excretion of protons and a decline in pH of the surrounding matrix. This tissue acidosis triggers a p53-mediated cell death of neighbouring healthy cells (Williams et al, 1999;Park et al, 2000). Tumour cells survive due to mutations in p53 or some other components in the apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in cyclin B1-Cdc2 kinase activity in the cells irradiated and treated with β-lap were similar to those in the cell treated with β-lap alone. We previously reported that an increase in the G2 cell population after irradiation increased the cyclin B1-Cdc2 kinase activity, which in turn, accelerated the exit of cells from the G2 phase to mitosis (21). It is tempting to conclude that the progressive decline in the G2 cell population after β-lap treatment removed the necessity for an increase in the cyclin B1-Cdc2 kinase activity in both non-irradiated and irradiated cells.…”
Section: Discussionmentioning
confidence: 91%
“…The supernatant was mixed with isopropanol (1:1) and stored overnight at -20 o C. After centrifugation at 12,000×g for 20 min, the pellet was resuspended in TE buffer (10 mM Tris-HCl pH 7.4, 1 mM EDTA) and the RNA digested by the addition of 0.2 mg/ml DNase-free RNase. A15~20μg aliquot of DNA from each sample, as well as the DNA molecular weight marker, were subjected to electrophoresis on 1.5% agarose gel in TBE (89 mM Tris base, 89 mM boric acid, 2 mM EDTA) and the DNA stained with ethidium bromide (21).…”
Section: Methodsmentioning
confidence: 99%